2022
DOI: 10.3389/fenvs.2022.821628
|View full text |Cite
|
Sign up to set email alerts
|

Improving Sustainable Field-Grown Wheat Production With Azospirillum brasilense Under Tropical Conditions: A Potential Tool for Improving Nitrogen Management

Abstract: Sustainable intensification of cropping systems requires to increase productivity and nutrients use efficiency while reducing negative impacts of agricultural management practices on ecosystem and environment. Plant growth-promoting rhizobacteria (PGPR) inoculations are considered one of the most promising and safe strategy to alleviate environmental alterations in context of climatic extremes to improve plant nutrition while reducing dependency of nitrogen (N) fertilizer application. This study investigated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 46 publications
(83 reference statements)
1
22
0
Order By: Relevance
“…significantly enhanced the growth of Arachis hypogea plant, protects plants from stress, and exhibits the production of ammonia and IAA (Gohil et al, 2022). Azospirillum brasilense reduces N fertilization, improves plant nutrition, and increases plant biomass and wheat grain yield as reported by Galindo et al (2022).…”
Section: Free-living Nitrogen-fixing Bacteriamentioning
confidence: 86%
“…significantly enhanced the growth of Arachis hypogea plant, protects plants from stress, and exhibits the production of ammonia and IAA (Gohil et al, 2022). Azospirillum brasilense reduces N fertilization, improves plant nutrition, and increases plant biomass and wheat grain yield as reported by Galindo et al (2022).…”
Section: Free-living Nitrogen-fixing Bacteriamentioning
confidence: 86%
“…Backer et al, (2018) show that inoculation with PGPR is considered one of the most promising and safe strategy and it has quite significant role in alleviation of environmental changes under the context of climate extremes and excessive use of fertilizer in agricultural soils. As well as Galindo et al, (2022) said that the inoculation of these microbes is recognized as one of the best and alternative strategy for ecofriendly crop-management techniques as it could improve plant nutrition on other hand reducing the dependence of N 2 fertilizer application.…”
Section: Effects Of Inoculation Of Isolated Microbial Strains Azospir...mentioning
confidence: 99%
“…Azospirillum brasilense has been reported to promote plant growth by increasing the production of phytohormones like gibberellins, auxins and cytokinins (Fukami et al, 2018, andGalindo et al, 2022). Santi et al, (2013) showed that phytohormones produced by bacteria thus enhance root branching and root elongation, which in turn favour the uptake of soil water and minerals and has a positive effect on plant growth, and Gibberellin produced by Azospirillum was found to play an important role in the early stages of plant growth in Graminae by enhancing shoot and root growth and increasing root-hair density.…”
Section: Effects Of Inoculation Of Isolated Microbial Strains Azospir...mentioning
confidence: 99%
“…Plants and microbial communities are the components of similar limited resources with a different relationship. However, plants assist microbial communities with available nutrients from the soil rhizosphere [ 18 ] and improve nitrogen mineralization, which can enhance the uptake of other nutrients for a higher performance and yield of plants [ 19 ]. The positive association (symbiosis) and negative association (pathogenesis) of the plant rhizosphere microbial community can affect nutrient availability and resource partition, thus increasing or reducing crop production, respectively [ 18 , 20 ].…”
Section: Introductionmentioning
confidence: 99%